HUBUNGAN SANITASI LINGKUNGAN DAN PERSONAL HYGIENE MAKANAN JAJANAN DENGAN KELUHAN PENYAKIT GANGGUAN PENCERNAAN (Gastrointestinal) PADA PEDAGANG DI SIMPANG KANDIS KOTA BENGKULU - Aplina Kartika Sari; Kinanti Dwi Widiarti; Yusmidiarti (Poltekkes Kemenkes Surabaya, 2023)
Food is a basic need for humans. Snack food is very likely to be contaminated due to lack of attention to environmental sanitation and personal hygiene when processing snack food with disease complaints at Kandis Simpang, Bengkulu City. The purpose of this study was to analyze the relationship between environmental sanitation and personal hygiene on traders' complaints of digestive disorders.This type of research is observational analytic with a cross sectional approach. The sample is 42 traders. The variables studied were environmental sanitation, personal hygiene and traders' complaints of digestive disorders. Data analysis used the chi square test.The results showed that 16.7% of traders had poor environmental sanitation, 26.2%of traders had poor personal hygiene and complaints of gastrointestinal diseases. The results of the chi-square test found that there was a relationship between environmental sanitation and gastrointestinal complaints with a significance value of P=Value 0.009 andthere was no relationship between personal hygiene and gastrointestinal complaints with a significance value of P=Value 0.021. There is a relationship between environmental sanitation and complaints of digestive disorders, but not with personal hygiene of traders. The researcher's suggestion for tradersis to understand the importance of environmental sanitation and personal hygiene for street food vendors at the Kandis intersection in Bengkulu City